2012
DOI: 10.1002/cncr.27608
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of mesenchymal‐epithelial transition factor gene (MET) and the catalytic subunit of phosphoinositide‐3‐kinase (PIK3CA) copy number elevation and correlation with outcome in patients with early stage breast cancer

Abstract: Purpose To determine the frequency and association with relapse-free survival (RFS) of MET and PIK3CA copy number elevations in early stage breast cancer. Methods Tumor DNA was extracted from 971 formalin-fixed paraffin-embedded early breast cancers for molecular inversion probes arrays. Data was segmented using the SNP-FASST2 segmentation algorithm. Copy number gains were called when copy number of each segment was greater than 2.3 or 1.7 respectively. RFS was estimated by Kaplan-Meier. Cox proportional haz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
41
3
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 33 publications
6
41
3
1
Order By: Relevance
“…In agreement with other studies, increased MET copy number was shown to be inversely correlated with ER status [9, 20]. It was thereby inversely correlated with the luminal A subtype, the least aggressive of the breast cancer subtypes, indicating that Met is more prominent in more aggressive subtypes.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In agreement with other studies, increased MET copy number was shown to be inversely correlated with ER status [9, 20]. It was thereby inversely correlated with the luminal A subtype, the least aggressive of the breast cancer subtypes, indicating that Met is more prominent in more aggressive subtypes.…”
Section: Discussionsupporting
confidence: 91%
“…It is unclear what is causing this overexpression, a common cause is known to be gene amplification. Previous studies have failed to find MET amplification in breast cancer [20, 21]; the present study showed MET amplification in only 8% of the tumours of two cohorts, and amplification did not correlate with protein expression. Although protein expression did not correlate with poor prognosis, increased MET copy number tended in both cohorts to be indicative of a shortened distant and loco-regional recurrence-free survival.…”
Section: Discussioncontrasting
confidence: 87%
“…Li et al . also showed a negative outcome for patients with tumors harboring PIK3CA mutations[3, 12]. In contrast, Maruyama et al ., Perez-Tenorio et al , and Kalinsky et al .…”
Section: Introductionmentioning
confidence: 99%
“…In both cohorts, MET and HGF were significantly correlated with each other (p<0.01). MET amplification has not been reported to be common in breast cancer, in the present study only 8% was found (Paper I) [138,139]. However, copy gain has been reported for MET in 27% HER2-positive metastatic breast cancer cases, as in the pre-and post-menopausal patients here, unrelated to subtype [140].…”
Section: Genes Of Interest In Breast Cancer Tumourscontrasting
confidence: 58%
“…Met and EGFR are reported to be involved in aggressive disease [138,153,156,[158][159][160]. An aggressive disease is indicated if the tumour is ER-negative, HER2-positive or triple-negative, and highly proliferative (as measured by NHG or S-phase fraction).…”
Section: Genes and Proteins In Relation To Clinicopathological Characmentioning
confidence: 99%